THE CONCEPT OF MANAGEMENT IN ENTERPRISE MANAGEMENT AND ITS SPECIFICITY - Kilichova Orzigul Zafar kizi; Urakova Mohinur O’lmas kizi; Sharipov Tulkin Saidahmedovich (International Journal of Innovations in Engineering Research and Technology, 2021)
This article presents practical suggestions and conclusions about the role of leadership in management, its further development and expansion in the context of the ever-growing importance of information and technology.